Pengembangan Media Pembelajaran FINTER (Fikih Interaktif) untuk Pembelajaran Fikih di MTs Bahrul Ulum Tambakberas Jombang - Ilyas, Hafidz; Nisa, Khoirun; Wahyudi, Wahyudi (MASALIQ, 2025)
Rapid developments are taking place in the realm of education in the 21st century. Teachers in this era are expected to have the ability to use technology in teaching at school and also be able to overcome various challenges that arise. To increase the effectiveness of learning, it is necessary to use interesting media. This research is entitled the development of FINTER Learning media (Interactive Fikih) for learning Fikih in class VIII MTs Bahrul Ulum Tambakberas Jombang. This research focuses on the development of Powerpoint-based Fikih learning media for Fikih subjects in class VIII MTs Bahrul Ulum Tambakberas Jombang. This research applies the research and development (R&D) method using the ADDIE model. The purpose of this research is to facilitate and make learning Jurisprudence subjects more interesting for teachers and students. This research produces learning media called FINTER. This media received a score of 88% from student responses. The results of the material expert validation received a score of 89% and 91% for media expert validation, thus FINTER media is very feasible to use in learning media at MTs Bahrul Ulum Tambakberas Jombang.